Brand positioning of Greenpeace through Social Media - Cabrera Brito, Andrea; Martín Critikian, Davinia; Viñarás, Mónica; Gonzálvez-Vallés, Juan Enrique (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The present work consists of analyzing the positioning of Greenpeace through its Social Networks. For which a previous investigation has been carried out in order to know the history and background not only of the organization, but also of the environmental movement, investigating various articles and reports from secondary sources. After this, the social platforms have been analyzed: Instagram and Facebook, to understand how it is perceived by its consumers according to which platform. Finally, some of the most popular strategies and campaigns of the organization have been analyzed and a proposal for improvement has been proposed.